HOW AND WHY IT IS REQUIRED TO STUDY HISTORY AT SCHOOL AS WELL AS AT UNIVERSITY? - Georgy A. Antipov (Moscow Polytechnic University, 2022)
The principle cultural contexts are considered, which are necessary to be taken into account in order to create "the single textbook of history". There should be included such things as commemorative practices, historical memory, scientific rationality. The clear understanding of their borders and forms of their representation in the historical textbooks is needed.